Intraoperative Fractions of Inspiratory Oxygen Are Associated With Recurrence-Free Survival After Elective Cancer Surgery - Dehne, Sarah; Spang, Verena; Klotz, Rosa; Kummer, Laura; Kilian, Samuel; Hoffmann, Katrin; Schneider, Martin A.; Hackert, Thilo; Büchler, Markus W.; Weigand, Markus A.; Larmann, Jan (Frontiers in Medicine, 2021)
Background: Choice of fraction of inspiratory oxygen (FiO2) is controversial. The objective of this analysis was to evaluate whether intraoperative FiO2 was associated with recurrence-free survival after elective cancer surgery. Methods and Analysis: In this single-center, retrospective study, we analysed 1084 patients undergoing elective resection of pancreatic (n=652), colorectal (n=405) or hepatic cancer (n=27) at Heidelberg University Hospital between 2009 and 2016. Intraoperative mean FiO2 values were calculated. For unstratified analyses, the study cohort was equally divided into a low- and a high-FiO2 group. For cancer-stratified analyses, this division was done within cancer-strata. The primary outcome measure was recurrence-free survival until last known follow-up. Groups were compared using Kaplan-Meier analysis. A stratified log rank test was used to control for different FiO2 levels and survival times between the cancer strata. Cox-regression analyses were used to control for covariates. Sepsis, re-operations, surgical site infections and cardiovascular events during hospital stay and overall survival were secondary outcomes. Results: Median FiO2 was 40.9% (Q1-Q3, 38.3-42.9) in the low vs. 50.4% (Q1-Q3, 47.4-54.7) in the high-FiO2 group. Median follow-up was 3.28 (Q1-Q3, 1.68-4.97) years. Recurrence-free survival was considerable higher in the high-FiO2 group (p<0.001). This effect was also confirmed when stratified for the different tumor entities (p=0.007). In colorectal cancer surgery, increased FiO2 was independently associated with increased recurrence-free survival. The hazard for the primary outcome decreased by 3.5% with every 1% increase in FiO2. The effect was not seen in pancreatic cancer surgery and we did not find differences in any of the secondary endpoints. Conclusions: Until definite evidence from large-scale trials is available and in the absence of relevant clinical conditions warranting specific FiO2 values, perioperative care givers should aim for an intraoperative FiO2 of 50% in abdominal cancer surgery as this might benefit oncological outcome.